Dynamic processes of the retrofited rear suspension of the vehicle - Bogdevičius, Marijonas; Junevičius, Raimundas (Transport, 2004)
The main aim of the investigation is to design rear suspension and to improve the dynamic characteristics of the vehicle. Three types of rear suspensions that consist of a leaf spring, a hydraulic and a pneumatic damper, an air spring are designed. The dynamic models of the quarter car with these rear suspensions are presented. Random disturbance of particular road surface is played back by using a spectral density and Monte Carlo method. Natural frequencies of rear suspension are presented. The dependence of standard deviations of the first, the second and the third derivates of particular random displacements on the vehicle speed is obtained. Dynamic characteristics of three rear suspensions are compared and the best rear suspension is determined.First Published Online: 27 Oct 2010